Resistance Test of Several Types of Local Rice to Fe Stress in the Nursery Phase - NURHAYATI, NURHAYATI; Ir.Rini Susana,M.Sc, Ir.Rini Susana,M.Sc; Dr.Tantri Palupi,SP.,M.Si, Dr.Tantri Palupi,SP.,M.Si (Jurnal Sains Mahasiswa Pertanian, 2019)
Nurhayati (1) ,Rini Susana (2) , Tantri Palupi (2)(1) Students of the Faculty of Agriculture and(2) Lecturer at the Faculty of Agriculture, Tanjungpura University PontianakEmail: nurhayatiaya099@gmail.com ABSTRACT Efforts to increase rice production include being able to use marginal land. One marginal land that can be used is tidal land that has not been used optimally to meet national food needs. The main problem in tidal land that is often encountered is the growth of plants experiencing disruption due to iron (Fe) poisoning. To get the type of rice that is suitable to be cultivated on marginal land can be done by using selection on water culture media. This study aims to look at the resistance of several types of local rice that are resistant to Fe stress in the nursery phase. This study began in April until June 2018 in the greenhouse of the Faculty of Agriculture, Tanjungpura University, Pontianak. The method used was Random Block Design (RBD) Single Factor with one factor, namely 10 types of rice consisting of 2 superior varieties of rice and 8 types of local rice with 3 replications. Each replication consists of 10 plant samples. The treatment in this study used 300 ppm Fe concentration. Observation variables consisted of crop scoring, seedling height, root length, number of leaves, number of tillers, dry weight of shoot and root dry weight. Based on the results of the study it can be concluded that application of Fe with 300 ppm concentration provides very severe stress on all types of rice tested, namely Asmo, Mandiri, Canting, Ringkak Samut, Ketumbar, Banjar, Galo, Dewi Ratih, Ciherang, and Inpara2. Scoring results show that all types of rice very severe leaf damage, the plants become dry and dead. It’s shows that all types of rice tested were not resistant to Fe stress with a concentration of 300 ppm. Keywords: iron stress, local rice, nursery phase